Hubungan Parenting Keluarga Dengan Pembentukan Karakter Religius Anak SD/MI di Dusun Krakal Dawung Wonosobo - Bagas Latif; Abdul Majid; Chairani Astina (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study aims to examine family parenting patterns, the level of religious character among elementary school children (SD/MI), and whether a significant relationship exists between the two variables in Krakal Dawung Hamlet, Kertek District, Wonosobo Regency. A quantitative correlational approach was employed using total sampling, involving 32 parent respondents. Data were collected through a Likert-scale questionnaire and analyzed using Pearson Product Moment correlation with SPSS 30. Descriptive analysis revealed a mean parenting score of 107.53 (moderate category) and a mean religious character score of 90.59 (good category). The correlation test yielded r = −0.023 with p = 0.903 (p > 0.05), indicating that H₀ is accepted. Therefore, there is no significant relationship between family parenting and the formation of religious character among elementary school children in Krakal Dawung. This finding suggests that children's religious character is shaped by factors beyond family upbringing, including the role of schools, Quranic learning activities (TPQ), peer interactions, and exposure to digital media.